Improvement of Soft Soil Using Linear Distributed Floating Stone Columns under Foundation Subjected to Static and Cyclic Loading - Mahdi O Karkush; Anwar Jabbar (Salehan Institute of Higher Education, 2019)
A stone column is one of the soil improvement methods that are mainly used for improving the geotechnical behavior of soft soils. For deep improvement of soft soil, the floating stone columns are considered the best and effective economically which provide lateral confinement and drainage and longitudinal skin friction. In this study, six tests were carried out on the natural soft soil of undrained shear strength of 5.5 kPa improved by single and two linear distributed floating stone columns. The stone column dimensions are 30 mm in diameter and 180 mm in length and the stone column material is sand of high internal friction angle of 48°. The natural and improved soil samples are tested under isolated raft foundation of dimensions 120×120 mm subjected to vertical static and cyclic loading of frequency 2Hz and continued for 50 seconds. The results showed a significant improvement in soil bearing capacity when reinforced with stone columns despite the small area replacement ratio, where the bearing capacity of improved soil increased by 120 to 145%. The compressibility of improved soil decreased by 57 to 86% in comparison with that of natural soft soil. Also, the floating stone columns reduced the porewater pressure, where the stone columns considered efficient in providing short drainage pathways. This can be one of the reasons why soil reinforced with floating stone columns hold higher cyclic and static stresses regardless the end bearing of stone columns.